Jingle, the Christmas clown - De Paola, Tomie (New York : Putnam's, 1992)
Staying behind when their circus moves on, a young clown and a troupe of baby animals put on a special Christmas Eve show for an Italian village too poor to celebrate the holiday.
Children's Catalog (Wilson)
Publisher's Weekly
*BOOKLIST*
3.5
K-3
Keywords: Clowns -- Fiction; Circus -- Fiction; Christmas -- Fiction; Animals -- Infancy -- Fiction; Clowns -- Fiction; Circus -- Fiction; Christmas -- Fiction; Animals -- Infancy -- Fiction; Italy -- Fiction